2009
DOI: 10.1007/s11606-009-0930-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient–Provider Communication About Sexual Health Among Unmarried Middle-aged and Older Women

Abstract: Some women felt that providers should ask about SHIR only if questions relate to an associated health problem (e.g. sexually transmitted infection). When providers do ask questions about SHIR, they should do so in ways that can be answered by all women regardless of partnering status, and follow questions with non-judgmental discussions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 38 publications
(38 reference statements)
0
48
0
Order By: Relevance
“…In this sample, women were more knowledgeable than men; however, this is not consistent with results found by Langer-Most and Langer (Langer-Most & Langer, 2010), who found that provider gender did not affect knowledge. Middle aged and older women have been found to be more comfortable talking about sexual health to female providers (Politi, Clark, Armstrong, McGarry, & Sciamanna, 2009). Perhaps this factor is influencing more female providers to learn about aging sexuality.…”
Section: Discussionmentioning
confidence: 99%
“…In this sample, women were more knowledgeable than men; however, this is not consistent with results found by Langer-Most and Langer (Langer-Most & Langer, 2010), who found that provider gender did not affect knowledge. Middle aged and older women have been found to be more comfortable talking about sexual health to female providers (Politi, Clark, Armstrong, McGarry, & Sciamanna, 2009). Perhaps this factor is influencing more female providers to learn about aging sexuality.…”
Section: Discussionmentioning
confidence: 99%
“…Although patients generally feel that clinical settings are an appropriate place to discuss sexual health and would like their providers to initiate such discussions, providers often have difficulty adequately addressing sexual health issues for a number of reasons, including provider reticence and a lack of training. 25,28 In many cases, current training and educational materials may benefit from revision to help providers navigate the difficult balance between acknowledging the seriousness of sexual health issues and avoiding overemphasis of negative consequences. 29 When patients do experience sexual health problems, it may be helpful for providers to encourage them to move away from blaming others and to focus on enhancing their own health and reducing future risks.…”
Section: Education and Training Of Health-care Providersmentioning
confidence: 99%
“…Perceptions of relevancy tended to be associated with gynecological or sexual health complaints. In contrast, complaints that were non-gynecological in nature (e.g., sore throat, broken leg) were perceived by some as irrelevant to disclosure (Edwards & van Roekel, 2009;Politi et al, 2009; see Table 2 for patient attributes).…”
Section: Perceived Relevancymentioning
confidence: 99%
“…It may be important for HCPs asking for sensitive information such as sexual orientation to explain why it is essential for them to know about this, and to what use this information will be put, in order to alleviate privacy concerns. Importantly, these discussions may influence lesbian patients' perceptions regarding the relevancy of their disclosure, particularly in situations that do not involve gynecological or sexual health problems (see Politi et al, 2009 for a qualitative analysis focusing on the experiences of older women, some of whom preferred health professionals to inquire about sexual history only when relevant).…”
Section: Implications For Primary Healthcare Providersmentioning
confidence: 99%